Membangun Desa Digital: Implementasi Sistem Metadesa dalam Program Smart Village di Provinsi Lampung - Angga Natalia (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
This study analyzes the implementation of the Metadesa System within the Smart Village Program in Lampung Province, which aims to improve the quality of rural life through the utilization of information and communication technology (ICT). The Metadesa System functions to integrate data across administrative levels village, sub-district, district, and province while supporting public services that are more transparent, accountable, and efficient. Focusing on three main pillars, namely Smart Government, Smart Economy, and Smart People, this study evaluates the effectiveness and challenges of implementation using an evaluative approach, covering aspects of communication, resources, implementers' attitudes, and bureaucratic structure. The findings indicate that the implementation of the Metadesa System has contributed to improved public service efficiency and community empowerment, despite facing challenges such as limited internet infrastructure and low digital literacy in certain areas. The urgency of this study lies in the need to accelerate rural digital transformation to reduce development disparities and strengthen data-driven governance. It is recommended that the development of human resource capacity, along with sustained policy and technological infrastructure support, be prioritized to enable the replication of successful implementation in other regions.